The Female Genital Tract Microbiome Is Associated With Vaginal Antiretroviral Drug Concentrations in Human Immunodeficiency Virus–Infected Women on Antiretroviral Therapy. (5th October 2017) - Donahue Carlson, Renee; Sheth, Anandi N; Read, Timothy D; Frisch, Michael B; Mehta, C Christina; Martin, Amy; Haaland, Richard E; Patel, Anar S; Pau, Chou-Pong; Kraft, Colleen S; Ofotokun, Igho
Abstract : Three major microbiome community types (mCTs) were identified in the female genital tract (FGT) of HIV-infected virologically suppressed women on antiretroviral therapy. Certain FGT mCTs were associated with decreased FGT antiretroviral concentrations in women on tenofovir disoproxil fumarate/emtricitabine and ritonavir-boosted atazanavir. Abstract: Background: The female genital tract (FGT) microbiome may affect vaginal pH and other factors that influence drug movement into the vagina. We examined the relationship between the microbiome and antiretroviral concentrations in the FGT. Methods: Over one menstrual cycle, 20 human immunodeficiency virus (HIV)–infected women virologically suppressed on tenofovir (TFV) disoproxil fumarate/emtricitabine and ritonavir-boosted atazanavir (ATV) underwent serial paired cervicovaginal and plasma sampling for antiretroviral concentrations using high-performance liquid chromatography–tandem mass spectrometry. Analysis of 16S ribosomal RNA gene sequencing of cervicovaginal lavage clustered each participant visit into a unique microbiome community type (mCT). Results: Participants were predominantly African American (95%), with a median age of 38 years. Cervicovaginal lavage sequencing (n = 109) resulted in a low-diversity mCT dominated by Lactobacillus (n = 40), and intermediate-diversity (n = 28) and high-diversity (n = 41) mCTs with abundance of anaerobic taxa. In multivariable models, geometric mean FGT:plasma ratios varied significantly by mCT for all 3 drugs. For both ATV and TFV, FGT:plasma was significantly lower in participant visits with high- and low-diversity mCT groups (all P < .02). For emtricitabine, FGT:plasma was significantly lower in participant visits with low- vs intermediate-diversity mCT groups ( P = .002). Conclusions: Certain FGT mCTs are associated with decreased FGT antiretroviral concentrations. These findings are relevant for optimizing antiretrovirals used for biomedical HIV prevention in women.